Apatite geochemistry as a proxy for porphyry-skarn Cu genesis: a case study from the Sanjiang region of SW China - Liu, Qian; Pan, Li-Chuan; Wang, Xin-Song; Yan, Jun; Xing, Lang-Zhang (Frontiers in Earth Science, 2023)
In view of the importance of the magmatic oxidation state and volatile composition (H2O-S-Cl) in porphyry Cu mineralization, identification of magmatic information has become the basis for the evaluation of the Cu-mineralization potential of porphyries. Apatite, as a common accessory mineral in porphyry, is recognized as an effective petrogenetic and metallogenic indicator. In this study, we analyze the in situ major and trace elements and Nd isotope content of apatite from four granitic plutons in the Yidun Terrane, SW China, in order to provide new insights into the identification of the magmatic features of Cu-mineralized plutons. The plutons investigated in this study are a Cu-mineralized pluton (Hongshan) and three non-mineralized plutons (Cilincuo, Rongyicuo, and Hagela). Chemical composition and textural analysis indicate that the apatites are all of magmatic origin and have not been altered. Our results show that apatite δCe values rather than δEu and Ga values are more valid indicators of the magma oxidation state of the four plutons. Based on apatite δCe values and zircon compositions, the parental magma of the Hongshan pluton is identified as having been more oxidized than those of the other three plutons. Moreover, the higher Cl content (0.06–0.23 wt%) in the Hongshan apatite compared to that in apatite from the other three plutons (0.01–0.09 wt%), indicates that the parental magma of the former pluton was more enriched in Cl. Apatite from the Hongshan pluton contains more SO3 (average 0.05 wt%) than that from the other three plutons (SO3 content mostly lower than the detection limit of electron probe micro-analysis), which may be related to higher magmatic oxygen fugacity of the Hongshan pluton. In addition, the Nd isotopic composition of apatite [εNd(t): −13.6−5.9] demonstrates that the Cu-mineralized and non-mineralized plutons were derived from the melting of ancient lower crust. Furthermore, based on the geochemical signature of adakite revealed by apatite Sr/Y and δEu values, the Hongshan pluton can be considered to have been produced as the result of partial melting of the thickened lower crust. Finally, an index system consisting of apatite δCe, Sr/Y, and F/Cl values is established to distinguish between the Cu-mineralized and non-mineralized plutons.